Effect of Black Cumin and Arjuna Fruit Extract on Lipid Oxidation in Pork Nuggets during Refrigerated Storage - Chauhan, Pranav; Das, Arun K.; Das, Annada; Bhattacharya, Dipanwita; Nanda, P. K. (Journal of Meat Science, 2019)
In this study, the efficacy of arjuna fruit extract (AFE, 1.0 %) and black cumin extract (BCE, 1.5%) in retarding lipid oxidation of pork nuggets was investigated and compared with a synthetic antioxidant, butylated hydroxytoluene (BHT, 100 ppm) and control sample during refrigerated storage at 4±1oC for 20 days under aerobic packaging. The total phenolics content of AFE treated cooked pork nuggets was significantly (p < 0.05) higher compared to control but nuggets with BCE extract had comparable total phenolics with BHT treated nuggets. However, incorporation of AFE, BCE or BHT did not have any effect on the cooking yield of pork meat nuggets. The increase in pH during storage was significantly (p>0.05) less in all treated samples as compared to control. The pork nuggets with AFE had significantly (p<0.05) lower mean total aerobic plate count than control. In samples incorporated with AFE and BCE, thiobarbituric acid reactive substances (TBARS) value, peroxide formation, free fatty acids were significantly (p<0.05) lower than control even on 20th day of storage. Sensory evaluation revealed that incorporation of AFE and BCE improved the flavour and overall acceptability scores of pork nuggets than control and prolonged the shelf-life of the product up to 20 days by inhibiting lipid oxidation and microbial growth. From the above findings, it is concluded that AFE at 1 % and BCE at 1.5 % were effective and could be used as natural antioxidant in retarding lipid oxidation of processed muscle foods.